Frescoes of the Church of Christ in Veroia (1314–1315) and the Issues of George Kalliergis’ Oeuvre - Iakovleva, Maria I. (Actual Problems of Theory and History of Art, 2017)
The small single-nave Church of Christ in Veroia, which used to be the katholicon of the Resurrection monastery, retains a complete and accurately dated frescoes ensemble of the Early Palaeologan period. A dedicatory inscription above the western entrance reports that the church was painted by the artist named Kalliergis, “the best painter in all of Thessaly”, and consecrated by the Constantinopolitan patriarch during the reign of the Emperor Andronikos II Palaeologos in 1314–1315.In 1955, in reliance with this inscription, the stylistic and iconographic features of the frescoes, A. Xyngopoulos suggested that the painter who carried them out was connected with Thessaloniki, whose cultural influence extended to Veroia. This hypothesis was later confirmed by a certain document of Hilandar Monastery on Mount Athos, dated to 1322. Wide range of issues associated with the frescoes of the Church of Christ in Veroia is of particular importance since their creation time and author are precisely known, and therefore the examination of this monument can improve our concept of the evolution of Byzantine painting during the Early Palaeologan period.The article deals with three key aspects connected with the frescoes of the Church of Christ. Firstly, the murals of the church demonstrate a number of specific iconographic features that are based, in our opinion, on the artistic vision of Kalliergis. So, the preference which is given to succinct iconographic variants can be explained by the painter’s desire to enrich the meaning of the image, without overloading it with excessive details, and to preserve the possibility of clear perception of the entire composition. Secondly, the creative manner of Kalliergis had its individual features that distinguish him from other contemporary painters. Thus, Kalliergis is a master of a compact, restrained and balanced composition; he avoids narrative even in the most dramatic scenes. This manner contradicts with the great part of monuments in Macedonia and Serbia created at the end of the 13th — beginning of the 14th century which, in G. Millet’s apt words, “have a sense of drama” and demonstrate dynamism and redundancy in narrative scenes. Kalliergis isa true muralist, who consistently embodies the principle of clear and proportional division of the architectural space. His paintings, along with frescoes in the nave of the Church of the Holy Apostles in Thessaloniki(ca. 1314), belong to the most aristocratic trend in the Byzantine art of the first quarter of the 14th century.Finally, the issue of attribution of the monuments that can be more or less likely attributed to Kalliergis still remains. The article summarizes opinions of different researchers on this uneasy question, which are often based on vague stylistic (or even purely iconographic) criteria and need further examination.